EVALUASI RENCANA TATA RUANG WILAYAH KOTA BANDA ACEH BERBASIS MITIGASI BENCANA TSUNAMI - , Insun Kesuma Wijaya ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Tsunami in 2004 had destroyed 27 % of 60.333 sq km Banda Aceh into a land without buildings and loss of life lost and dying world reached 27,000 souls from the 243 895 residents of Banda Aceh. Spatial planning Banda Aceh in 2003 was revised to Spatial Banda Aceh 2009 after tsunami in December 26, 2004 because there has been a change of spatial and no mitigation of tsunami in Banda Aceh Spatial plan 2003. The method work research was conducted with a qualitative evaluation approach. This method aims to unify things behind perception of essence the Banda Aceh city spatial mitigation. Type is descriptive formative evaluation that focuses on quality of information collection program activities and results. Effect of disaster mitigation (2004, tsunami) spatial achievements in Banda Aceh as a whole reached 70.5 % and 29.5 % has not been achieved. Some of the problems that affect implementation of disaster mitigation as a major aspect in preparation in spatial plan Banda Aceh: (1) development plan is done in original area, (2) does not include a map of tsunami risk, (3) development be on site before tsunami, and (4) appropriate tread road early form because of limited funds, land ownership, land constraints, the programs that have been made like before tsunami with a large capital investment, and condition of building and housing can still be used to form a pattern of settlements built before tsunami which has linkages between process performed in past and current implications. Factors affecting the implementation of disaster mitigation as a major aspect in the preparation of Spatial plan Banda Aceh are: a long time process compilation, emergency situations, limited scientific data, inconsistencies plans, changes in legislation, and political considerations.